ANALISIS ZAT RHODAMIN B PADA SAUS TOMAT YANG BEREDAR DI KANTIN KAMPUS UNIVERSITAS HALU OLEO KENDARI - lisnawaty lisnawaty (Universitas Widya Gama Mahakam Samarinda, 2020)
Background: Food coloring is a food additive in the form of natural dyes and synthetic dyes when applied to food, able to give or improve color. rhodamine B is a synthetic dye that is very dangerous when inhaled, exposed to eyes or skin, and is swallowed. Of the 34 canteens at Halu Oleo University, all use tomato sauce and some are suspected of containing rhodamine B with bright and more conspicuous color characteristics. Objectives: This study aimed to analyze synthetic dye of rhodamine B in tomato sauce circulating at the canteen of Halu Oleo University, Kendari. Research Metodes: The type of study was descriptive. The population in this study was all types of tomato sauce used in 34 canteens of the Halu Oleo University, and the samples were 13 canteens obtained using the purposive sampling technique. Measurement of rhodamine B using test kits of rhodamine B. Results: The results showed that from 13 types of tomato sauce samples tested with test kits of rhodamine B by adding reagent (SbCl5 and Methyl Benzene) found 12 samples that did not change color (clear) means it did not contain rhodamine B (negative). But there was 1 sample of tomato sauce that changes color (purple), it means the tomato sauce was positive containing rhodamine B. The spectrophotometric test results obtained the amount of rhodamine B contained in the sample as many as 30.46842 ppm. Conclusion: Of the 13 canteens sampled, there was 1 canteen that used tomato sauce containing rhodamine B. Keywords: Rhodamine B, tomato sauce, canteen